2012
DOI: 10.1186/1472-6963-12-463
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence, emotional labor, and job satisfaction among physicians in Greece

Abstract: BackgroundThere is increasing evidence that psychological constructs, such as emotional intelligence and emotional labor, play an important role in various organizational outcomes in service sector. Recently, in the “emotionally charged” healthcare field, emotional intelligence and emotional labor have both emerged as research tools, rather than just as theoretical concepts, influencing various organizational parameters including job satisfaction. The present study aimed at investigating the relationships, dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
59
2
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 54 publications
(79 reference statements)
9
59
2
5
Order By: Relevance
“…In research, Psilopanagioti et al (2012), self-awareness of the factors that elicit particular emotions permits physicians to act in the most appropriate way to enhance job satisfaction. However, the results of this study showed different results from that of a previous study.…”
Section: A Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In research, Psilopanagioti et al (2012), self-awareness of the factors that elicit particular emotions permits physicians to act in the most appropriate way to enhance job satisfaction. However, the results of this study showed different results from that of a previous study.…”
Section: A Discussionmentioning
confidence: 99%
“…Wong & Law (2002), who viewed EI as consisting of self-emotion appraisal, others' emotional appraisal, use of emotion, and the regulation of emotion, suggested that EI is a core variable that affects the performance of leaders. More recently, Higgs (2004), Anari (2012), Psilopanagioti et al (2012), and Hanzaee & Mirvaisi (2013) confirmed a positive association between employee EI and job performance. Psilopanagioti et al (2012) suggested that EI (self emotion appraisal, others' emotion appraisal, regulation of emotion, use of emotion) appears to play a critical role in job satisfaction about human interaction.…”
Section: ⅱ Literature Review and Hypothesis Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, (Psilopanagioti and Niakas, 2012) stated that emotional intelligence is very important for organization service sector outcome (Gunavathy & Ayswarya, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Explored that job satisfaction is important for both levels (organization and individual) also Job performance have same importance, Individuals should competent in control their emotions under pressure and stress and through constraints (Psilopanagioti et al, 2012) find these contributing good understandings of emotional parameters that affect the process of work in are increasing in the service and its quality.…”
Section: Introductionmentioning
confidence: 99%